(untitled) (Gaceta Técnica, 2017)
Local roads in Lara state, Venezuela, have been deteriorating progressively due to the lack of a scheduled maintenance plan by the authorities. Particularly, it is believed that the current situation of L003 LA road is consequence of the absence of information about both physical and functionality conditions of drainage system, state of the road signs, poor condition of the pavement, and other troubles about geometric parameters. Therefore, it was created a data base based in topographic planes studies of its transversal section, development of a PCI evaluation of its pavement and the inspection of its geometrical design. This data base was run in a system of geographical information so that it would be possible to update all the information periodically. Additionally, it was proposed a plan of improvements for 29.10 km of the road, in which the PCI evaluation results were regular due to the poor conditions of the drainage system; and where the visibility and road signs were unsatisfactory.